Mamdani-Type Fuzzy-Based Adaptive Nonhomogeneous Synchronization - J. R. Pulido–Luna; J. A. López–Rentería; N. R. Cazarez–Castro (Complexity)
The aim of this work is the design of an adaptive controller based on Mamdani-type fuzzy inference systems. The input control is constructed with saturation functions’ fuzzy-equivalents, which works as the adaptive scheme of the controller. This control law is designed to stabilize the error system to synchronize a pair of chaotic nonhomogeneous piecewise systems. Finally, an illustrative example as numerical evidence is developed.